2013
DOI: 10.1371/journal.pone.0075381
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation at Serines 216 and 221 Is Important for Drosophila HeT-A Gag Protein Stability

Abstract: Telomeres from Drosophila appear to be very different from those of other organisms – in size and the mechanism of their maintenance. In the absence of the enzyme telomerase, Drosophila telomeres are maintained by retrotransposition of three elements, HeT-A, TART, and TAHRE, but details of their transposition mechanisms are not known. Here we characterized some biochemical characteristics of the HeT-A Gag protein encoded by the HeT-A element to understand this mechanism. The HeT-A Gag protein when overexpresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…The mechanism of selective interaction of mitotic kinases with HeT-A Gag cytoplasmic granules is unclear. HeT-A Gag is phosphorylated, which is important for the protein stability [78]. It has been reported that Cdk1 activity produces the docking sites for Polo recruitment to its targets [79][80][81].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of selective interaction of mitotic kinases with HeT-A Gag cytoplasmic granules is unclear. HeT-A Gag is phosphorylated, which is important for the protein stability [78]. It has been reported that Cdk1 activity produces the docking sites for Polo recruitment to its targets [79][80][81].…”
Section: Discussionmentioning
confidence: 99%